Physicochemical properties of raw cleaned edible bird’s nest after different primary processing including a new cleaning method - Yeo, Bee-Hui; Yaya Rukayadi; Wong, Shew-Fung; Tan, Chin-Ping; Lai, Oi-Ming (Penerbit Universiti Kebangsaan Malaysia, 2023)
Primary processing is the cleaning process of raw uncleaned (RUC) edible bird’s nest (EBN) into raw clean (RC) bird’s nest. In this study, three primary processing methods were used, including two methods commonly used in industry (semi-dry and wet methods) and a newly proposed method (semi-wet method). EBNs before and after primary processing were characterised by structural and chemical analysis. The RC EBN samples after initial processing were divided into two categories, with moulding (cup-shaped) and un-shaped. Scanning Electron Microscopy-Energy Dispersive X-ray Microanalysis (SEM-EDX) was used to study the morphology and element composition of EBN samples. The EBN sample were also tested on their colour, moisture content, water activity, nitrite content, nitrate content, total sialic acid content, total glycoprotein content, and total polysaccharide content. The semi-wet method yielded > 75% cup- shaped RC EBN for six different batches of RUC EBN, outperforming wet cleaning method (68.76 - 82.92%). Micrographs showed structural similarity between RC EBN samples even with different cleaning methods; but showed structural difference between RUC and RC EBN samples. Elements Na and Cl were significantly (P < 0.05) higher in RUC EBN. After cleaning, RC EBNs showed nitrite reduction at 34.78 - 60.72%; and nitrate reduction at 33.62 - 72.35%, respectively. No reduction of antioxidant activity, total sialic acid content, total glycoprotein content and total polysaccharide were observed for EBNs after primary processing. The nitrate and glycoprotein contents in EBNs after moulding were lower than those before moulding.